A Cross-Cultural Pragmatic Study of Advice-Giving in Jay Shetty and Fellexandro Ruby’s Youtube Monologue - Setiyowati, Reno (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
YouTube has become a widely used platform for creating and consuming self-development content, and its global reach makes it an interesting site to explore cross-cultural pragmatics. This study looks into the advice-giving strategies of two well-known speakers: Jay Shetty, a British-Indian content creator, and Fellexandro Ruby, an Indonesian-Chinese speaker. Using Brown and Levinson’s politeness theory, this research identifies the types of politeness strategies each speaker uses. To better understand the cultural background behind their choices, Wierzbicka’s cross-cultural pragmatic framework is also applied. The findings show that Jay Shetty tends to use more positive and negative politeness, framing his advice with empathy and relational tone. On the other hand, Fellexandro Ruby consistently delivers advice in an inclusive way, but often uses indirectness with the audience through personal story and reflection. These differences reflect how advice is shaped not only by individual speaking styles, but also by cultural values and audience expectations in different cultural settings.